Kesiapan UMKM Indonesia dalam Menghadapi Implementasi Indonesia–European Union Comprehensive Economic Partnership Agreement (IEU–CEPA) - Rifa Ardelia (Lembaga Pengembangan Kinerja Dosen, 2026)
The Indonesia–European Union Comprehensive Economic Partnership Agreement (IEU-CEPA) signed in September 2025 opens significant economic opportunities through the elimination of 98% of tariffs and broader access to the European Union market. However, the implementation of this agreement poses serious challenges for Micro, Small, and Medium Enterprises (MSMEs), which contribute 60% of GDP and absorb 97% of the national workforce. This research analyzes the readiness of Indonesian national law in supporting MSME participation in facing IEU-CEPA implementation using normative juridical methods with statutory and conceptual approaches. The research findings show that although IEU-CEPA offers 0% tariffs for 95% of Indonesian products, MSMEs face barriers in meeting European Union technical standards such as Technical Barriers to Trade (TBT), Sanitary and Phytosanitary Measures (SPS), and European Union Deforestation Regulation (EUDR). National regulations such as Law Number 20 of 2008 and Government Regulation Number 7 of 2021 have not yet regulated mechanisms for assisting MSMEs in meeting international standards, traceability systems, and special legal protection. The research recommends comprehensive legal harmonization and reform strategies including regulatory revision, establishment of an IEU-CEPA Task Force for MSMEs, adequate budget allocation, capacity building programs, and strengthening legal protection mechanisms to ensure MSMEs optimally utilize IEU-CEPA opportunities.